Change in cardiovascular risk profile in people with human immunodeficiency virus infection: a-12 months follow up - Lindayani, Linlin; Lai, Yiin; Ko, Wen Chien; Wang, Jung-Der; Ko, Nai Ying (Jurnal Ners, 2026)
Introduction: This study aimed to evaluate longitudinal changes in CVD risk and identify the contributing factors among HIV-positive individuals. Methods: A 12-month prospective study was conducted at an AIDS treatment center in southern Taiwan. A total of 411 adults living with HIV, aged 18 years or older, with no history of CVD treatment, were enrolled. CVD risk was assessed at baseline and 6 and 12 months using the D:A:D risk prediction model. Mixed-effects models were used to examine associated factors. Results: participants ranged in age from 19 to 77 years, with 95.9% being male. At baseline, 47% of the patients were low-risk, 37.7% were moderate-risk, 10.9% were high-risk, and 4.4% were very high-risk. After 12 months, 19% of participants showed a reduction in CVD risk. Increased risk was significantly associated with hepatitis C co-infection, use of lopinavir- or abacavir-based ART, and a longer duration of lopinavir exposure. Conversely, reductions in CVD risk were linked to higher educational attainment, use of antihypertensive or lipid-lowering therapy, and adherence to a Non-Nucleoside Reverse Transcriptase Inhibitor (NNRTI)-based antiretroviral therapy regimen. Conclusions: CVD risk in PLHIV is dynamic and modifiable. The use of NNRTI-based regimens and lipid-lowering therapies contributed to a significant risk reduction. Comprehensive integrated management strategies addressing both HIV infection and cardiovascular health are essential. Further research is needed on the cardiovascular effects of integrase inhibitors (INSTIs), particularly their long-term effects on lipid profiles and endothelial function.